HUBUNGAN ANTARA MUTASI DENGAN TINGKAT KEPUASAN KERJA AUDITOR DI KANTOR PUSAT BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA (BPK RI) JAKARTA - Mega Ayu Ratnaputri; Ida Wahyuni; Siswi Jayanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
Job satisfaction is very important to improve employee and organizational performance. Employees will have a positive feelings toward their work if their job satisfaction are high. One of some factors that influence job satisfaction is companies policy, inclulding job rotation. Job rotation is implemented to avoid job saturation, so that employees feel comfortable in working. The impact of job dissatisfaction are increasing of employees turnover and absenteeism. The purpose of this study was to determine the correlation of job rotation and level of job satisfaction of auditors at head office of Badan Pemeriksa Keuangan Republik Indonesia (BPK RI) Jakarta. This study used an explanatory research with cross sectional approach. Population of this study were 1.064 and the number of sample in this research were 90 respondents, where proportional random sampling technique was used to determine samples. Data were collected by interview. Brayfield Rothe Index (BRI) questionnaire was used as an intrument to determine variable in job satisfaction. Data were analyzed using Rank Spearmen test with a 0.05 significance level. The results of this study indicate that some 55.6% odf auditors at the headquarters of BPK RI have a high level of job satisfaction and 52.2% of auditors rate that implementation of job rotation at BPK RI are proper. From this study, it can be concluded that there’s correlation of job rotation and level of job satisfaction (p-value=0.003).